Critically appraised topic on adverse food reactions of companion animals (7): signalment and cutaneous manifestations of dogs and cats with adverse food reactions - Olivry, Thierry (BMC Vet Res, 2019)
BACKGROUND: Outside of pruritus, there is no clear consensus on the nature and prevalence of cutaneous manifestations of adverse food reactions (AFRs) in dogs and cats. RESULTS: We searched two databases on August 7, 2018, for articles reporting detailed data on the signalment and clinical signs of at least one dog or cat with a cutaneous AFR (CAFR). We identified 233 and 407 citations from which were selected 32 articles reporting original information. Twenty-two articles included data on 825 dogs with CAFRs. The reported age of onset varied from less than one to 13 years of age; a beginning of signs by 6 or 12 months of age was noted in 22 to 38% of dogs, respectively. The female-to-male ratio also varied considerably. Four breeds (German shepherd dogs, West Highland white terriers, Labrador and golden retrievers) accounted for about 40% of affected dogs. Most dogs diagnosed with a CAFR were pruritic, most often in a generalized pattern, with the ears, feet, and abdomen also being frequently affected; the perineum was uncommonly targeted, however. Canine CAFRs presented mainly as recurrent bacterial skin infections, otitis externa and atopic dermatitis. Twelve articles reported novel information on 210 cats with this syndrome. There was no apparent breed and gender predisposition for feline CAFRs, but cats appeared to develop signs later than dogs with the same syndrome. Most cats with a CAFR were pruritic, especially on the head/face and neck, with the abdomen and ears also commonly involved. Symmetric self-induced alopecia, a head-and-neck self-traumatic dermatitis, miliary dermatitis and variants of eosinophilic diseases were the most common manifestations of feline CAFRs. CONCLUSIONS: CAFRs affect dogs and cats of any age, any breed, and both genders, with the proportion of juvenile dogs diagnosed about twice that of cats. There are no reliable breed predisposition data. Most patients are pruritic, with half the dogs having generalized pruritus and half the cats scratching their face/head or neck. Canine CAFRs most often manifest as bacterial skin infections, otitis externa or atopic dermatitis; cats with CAFRs will exhibit the expected clinical phenotypes associated with feline hypersensitivity dermatitides. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12917-019-1880-2) contains supplementary material, which is available to authorized users.